Protective effect of Ruta Chalepensis L. extract on oxidative stress and liver-kidney function induced by polymicrobial sepsis in rats (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Sepsis, a systemic inflammatory disease developed after an infectious insult and remains the major cause of death in intensive care units. The aim of this study was to examine the protective effect of the ethanolic extract of Ruta chalepensis L. (ERC) against oxidative stress and liver-kidney functions in cecal and ligation puncture (CLP) rats. In vitro, the results showed that ERC rich in phenolic compounds possessed important antioxidant activity. In vivo, CLP-induced oxidative stress evidenced by the increase of the TBARS and decrease in the enzymatic antioxidants (SOD, CAT, GPX) in liver and kidney. Moreover, CLP induced liver-kidney toxicities showed by an increase in the ALT, AST, PAL, LDH, BUN and creatinine in the plasma. However, the administration of ERC to CLP-rats prevents all these disorders. Positive action of ERC was confirmed by histo-pathological examination. Therefore this study suggests that ERC could be a potential therapeutic agent for sepsis treatment.